(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present work is presented in five chapters entitled Physicochemical Studies of Some Metal Complexes with O, NS donor legends. Below, a chapter wise summary is given. It deals with the introduction of the chemistry of coordination and briefly with theories. In this section, an account of Schiff bases, their metal complexes and their significance was discussed. A brief review of the literature on previous studies on thiosemicarbazone metal complexes and their stereochemistry, coordination mode study. Related schemes have been incorporated for the substituted thiosemicarbazones related to the present work. The aim of the present investigation has been outlined at the end of this topic.